Internal Control Pada Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas Dalam Perencanaan Dan Pengendalian Keuangan - ANGGRAINI, DESY ISMAH; Kusuma, Pramandyah Fitah; Rosidah, Amanatur (Politeknik Negeri Ambon, 2023)
This research aims to find out whether internal control related to cash receipts and disbursements is running effectively or not. As well as to find out whether the internal control of the Financial Planning and Control System is in accordance with authorization from UD management. Dadhen Kurnia Abadi. This type of research is qualitative research with the data analysis technique used is descriptive analysis technique. Data was obtained by conducting interviews, observation and documentation. The results of the research show that the accounting information system for cash receipts and disbursements running at UD. Dadhen Kurnia Abadi cannot be said to be good because it still uses manual recording which results in weaknesses, namely discrepancies in recording so that the information produced is not accurate and precise and does not rule out the possibility of abuse of authority or embezzlement of funds. So internal control is not yet running effectively because there is no cutoff from the job desk for each function.